Training and Educating of Pineapple Farmers in Producing Organic Fertilizer Using The Bio-EM4 Application Technology in Lendang Nangka Utara Village, Masbagik, East Lombok - Kisman Kisman; I Ketut Ngawit; Suprayanti Martia Dewi (Pascasarjana Universitas Mataram, 2024)
The aim of this community service activity is to train and mentor farmers to produce organic fertilizer from cattle pen waste to create a village community that is self-sufficient in meeting the fertilizer needs for its pineapple farming business. The activity used a participatory action method, which was carried out for 19 months. The results of the activities show that the implementation of the activities ran smoothly and successfully. Farmers' participation and enthusiasm, which was previously moderate, turned out to be increased to high after implementing direct assistance in the field. Farmers' knowledge and skills are increasing as evidenced by the fertilizer produced based on SNI standards which is classified as good quality. Organic fertilizer produced by farmers can be used as a substitute for Urea, ZK and TSP fertilizer because application of a dose of 25 tons ha-1 plus NPK Ponska dose of 100 kg ha-1 can balance the growth and yield of pineapple in plots fertilized with NPK dose of 500 kg ha-1 . So the recommended application dose for organic fertilizer produced by this program is 25 tons ha-1 plus NPK Ponska 100 kg ha-1 with the application time after soil processing.